Analisis Faktor-faktor yang Mempengaruhi Perilaku Konsumen Warung Lesehan di Kota Yogyakarta - Jemadi Jemadi; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2015)
Research with the title: "Analysis of Factors Affecting Consumer Behavior Warung Lesehan in Yogyakarta", aims to investigate the characteristics of consumers shop Lesbian and to determine the factors that influence consumer behavior lesehan food, when seen from the income factor, location, service , hygiene, recreation, price and location or a shop selling lesehan, as well as to determine the most dominant influence on consumer behavior lesehan food. In this study the factors thought to influence consumer behavior is limited in six factors: income, service, hygiene, recreation, price and location / place to sell. Analyzers in this study consisted of two kinds: First analysis of descriptive is to kengetahui consumer characteristics seen from the gender (male, female), national origin (DIY, outdoor DIY), age (less than 20 years old, 20-30 years, 30-40 years, 40-50 years above 50 years), education (junior high, high school, PT), employment (Private employees, civil servants, Self Employed, Military / Police, Student), obtained the following results: a) Based on the sex of the respondents , 90 respondents or 60 % are female, and male gender, the number of 60 respondents or 40%. b) Based on the age of respondents, mostly aged 20-30 years is 66 respondents (44 %), second younger than 20 years as many as 30 respondents (20%), were the least respondents aged greater than 50 years is 14 or 9,3%. c) By level of education, most high school education is 72 respondents or 48% then higher education as much as 38 or 25.3%, while the least no school/SD by 10 or 6.7%. d) The work is based on a student/students as many as 68 respondents, or 45.3%, followed by the order to two civil servants as much as 34 or 22.7% and the smallest farmers as much as 6 respondents or only 4%. e) By region of origin, from the outside DIY as many as 104 or 69.3% while the DIY as much as 46 or 30.7%. Medium to find out if there is a significant relationship between the factors that influence consumer behavior (itensitas purchases) using Chi Square. From 150 responden as samples, taken from 10 stalls lesehan with acidental sampling method, the results are as follows: a) X2 is based on the analysis of all factors (revenue, location, taste, hygiene, recreation/entertainment and price) of all effect/no relationship to consumer behavior Lesbian stalls in the city of Yogyakarta. b) Factors most powerful influence on consumer behavior is a recreation/entertainment, shows that the stall lesehan seen not merely a place to eat but has become an arena/place amuse yourself/recreation for consumers, while the population is all consumers shop cross-legged in the city of Yogyakarta. This research is expected to generate outputs in the form of Scientific Publication in the Journal of Air ISSN and local seminars.